Viral suppression among persons living with HIV in Trinidad & Tobago: Implications for targeted prevention programmes. Issue 11 (2nd November 2019) - Edwards, R. Jeffrey; Cyrus, Elena; Bhatt, Chintan; Lyons, Nyla; Lavia, Leon-Omari; Boyce, Gregory
ABSTRACT: In Trinidad and Tobago, despite persons living with HIV (PLHIV) having access to subsidised treatment and care, only 47% PLHIV attain viral suppression. The study assessed the role of individual-level factors on viral suppression among PLHIV in Trinidad and Tobago. Data from 9, 629 PLHIV who attended an HIV clinic between 2016 and 2018 were analysed. Cases were aged ≥18 who met the CDC HIV case definition. Viral suppression defined as a viral load of <200 copies/ml at last assessment. The chi-square test of association determined statistically significant relationships between individual factors and viral suppression. Logistic regression was used to estimate odds ratios (OR) for viral suppression. PLHIV who were males (OR = 0.76, 95% CI 0.67–0.87), men who have sex with men (MSM) (OR = 0.82, 95% CI 0.67–0.99), single/unmarried (OR = 0.69, 95% CI 0.55–0.87), aged 18–24 years (OR = 0.66, 95% CI 0.49–0.89), aged 25–49 years (OR = 0.81, 95% CI 0.70–0.94) were less likely to achieve viral suppression. These study findings demonstrate that retention/adherence programmes must urgently identify and target vulnerable PLHIV populations in Trinidad and Tobago to improve viral suppression. Further research examining community and societal factors, such as stigma and discrimination, is warranted.